Fétiche et football à Kisangani. Apport de comité de recherche au sein des clubs de l’Entente Urbaine de Football de Kisangani (EUFKIS). - King, LOMBEYA BOINDA (IJRDO - Journal of Social Science and Humanities Research, 2018)
This article is devoted on the practice of fetish by clubs of soccer to Kisangani. it had wanted knowledge so these clubs deliver himself to the practice of fetish but also if this fetish has a positive or negative impact on the result of match delivered. The existence of research committee confirmed by investigated them proves that the practice of fetish is a reality within several clubs of soccer of Kisangani. This committee of research, no formal, has for task to contact the fetish man capable to make win clubs of soccer at the time of match. To the question to know if often the fetish brings a positive result in favor of the team that solicits it, players were more numerous (18 investigated) to believe there against 9 supporters and 8 leaders. It shows players how much, in spite of practices of before the match as well as a good coaching doesn’t arrive to reassure them. As main actors of soccer on the lawn, this position of players of soccer of worried Kisangani in the measure where it could influence negatively on the development of soccer because footballers are more minded to trust the occult practices rather than to concentrate to work. If players were the first to believe that the fetish procures still the victory, this time is himself leaders of soccer clubs who are opinion that the link between the fetish and results of matches are minimal. While throwing the stroke of spotlight on supporters, it noticed that they have some measured positions so much in relation to effects positive or negative of fetishes on their teams. These results prove that supporters wish a certain performance and a certain effort on behalf of their teams in place to search for fetishes.